Fiscal Politics in the Euro Area - Eyraud, Luc (IMF Working Papers; Working Paper ;, 2017)
This paper provides evidence of fiscal procyclicality, excessive deficits, distorted budget composition and poor compliance with fiscal rules in the euro area. Our analysis relies on real-time data for 19 countries participating in the euro area over 1999-2015. We look for, but do not find, conclusive evidence of bias in procedures in relation to country size. The paper also briefly reviews the literature on political economy factors and policy biases, and offers some reflections on the euro area architecture.